2005
DOI: 10.1002/art.21079
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection in psoriatic arthritis

Abstract: Objective. To evaluate the prevalence of hepatitis C virus (HCV) infection in patients with psoriatic arthritis (PsA), compared with patients affected by non HCV-related rheumatic degenerative disorders. Methods. One-hundred consecutive subjects with PsA, and a statistically comparable group of 100 consecutive patients with peripheral osteoarthritis (OA) or sciatica due to L4 -L5 or L5-S1 herniated disc were tested for HCV infection with a third-generation microparticle enzyme immunoassay (MEIA). Positive case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…There is conflicting data on the association between HCV infection and psoriasis/psoriatic arthropathy independent of IFN‐α therapy. Studies have found no association between HCV infection and psoriasis 41,42 or psoriatic arthropathy, 43 an association between HCV infection and psoriatic arthropathy but not psoriasis, 44 or a statistically higher prevalence of HCV infection in patients with psoriasis 45–47 . In a recent multivariate analysis of over 12 000 patients, the prevalence of hepatitis C in psoriatic patients was 1.03%, compared with 0.56% in controls ( P < 0.001) 47 .…”
Section: Discussionmentioning
confidence: 97%
“…There is conflicting data on the association between HCV infection and psoriasis/psoriatic arthropathy independent of IFN‐α therapy. Studies have found no association between HCV infection and psoriasis 41,42 or psoriatic arthropathy, 43 an association between HCV infection and psoriatic arthropathy but not psoriasis, 44 or a statistically higher prevalence of HCV infection in patients with psoriasis 45–47 . In a recent multivariate analysis of over 12 000 patients, the prevalence of hepatitis C in psoriatic patients was 1.03%, compared with 0.56% in controls ( P < 0.001) 47 .…”
Section: Discussionmentioning
confidence: 97%
“…A total of 11 studies, including 3 case control and 8 cross-sectional studies with 25,047 psoriasis patients and 4,091,631 controls provided data for this outcome [22][23][24][25][26][27][28][29][30][31][32]. We identi ed substantial statistical heterogeneity across these 11 studies (I 2 = 89%).…”
Section: Association Of Psoriasis With Hepatitis C In Studiesmentioning
confidence: 99%
“…An association between hepatitis C and psoriasis was first noted in 1995 by Yamamoto et al 24 While the prevalence of psoriasis in hepatitis C patients has not been shown to be significantly increased, 21,[25][26][27] there is conflicting data on the prevalence of HCV infection in psoriasis and psoriatic arthropathy patients (Table 3). Studies have found no increase in the rate of HCV infection in patients with psoriasis or psoriatic arthropathy, [28][29][30][31] while others have found increased HCV infection in patients with psoriatic arthropathy, but not psoriasis. 32 In contrast, multiple studies have found a statistically higher prevalence of HCV infection in patients with psoriasis.…”
Section: Discussionmentioning
confidence: 99%